¿Cierran los números con la gente adentro? - Sacco Zeballos, Nicolás (El Colegio de México A.C., 2017)
Based on the theoretical-methodological branch of demographic data evaluation, the article estimates the population coverage of Argentina’s 2010 population census. Complementing other research, this study provides an estimate of housing and household coverage based on information published by the National Institute of Statistics and Censuses. The omission recorded is low for the general average of Latin America, but high compared with the 1980 and 1991 census rounds, with a lack of transparency in the results-building processes at various levels.